Cytoskeleton and ECM tumor mutant peptides: Increased protease sensitivities and potential consequences for the HLA class I mutant epitope reservoir. Issue 5 (2nd November 2017) - Callahan, Blake M.; Patel, Jay S.; Fawcett, Timothy J.; Blanck, George
Abstract : Cytoskeleton and extracellular matrix‐related proteins (CECMPs) represent the most common class of cancer mutants, owing to the large size of their coding regions and the randomness of mutagenesis. We used a bioinformatics approach to assess the impact of amino acid (AA) substitutions on the sensitivity of CECMPs to proteases relevant to melanoma and on the binding affinities for HLA class I. CECMP peptides with AA substitutions overwhelmingly reflect increased sensitivity to proteases implicated in melanoma development (MME, CTSS, MMP2, CTSD, CTSL) in comparison to the wild‐type peptide sequences. Furthermore, peptides with AA substitutions representing increased peptide protease sensitivity also represented relatively high binding affinities for HLA class I allelic variants. These analyses raise the question of whether increased protease sensitivity, of mutant cancer peptides represents a significant increase in the availability of cancer mutant, HLA class I epitopes and a hitherto unappreciated aspect of cancer cell immunogenicity, particularly in the case of melanoma? Abstract : What's new? Cytoskeleton and extracellular matrix‐related proteins (CECMPs) represent the most common class of cancer mutants, owing to the large size of their coding regions and the randomness of mutagenesis. This bioinformatics study assessed the impact of amino acid substitutions on the sensitivity of CECMPs to proteases relevant to melanoma—one of the most immunogenic cancers—and on binding affinities for HLA class I. The data suggest a striking increase in the protease sensitivity of CECMP mutant peptides, and a strong correlation between mutant peptides with increased protease sensitivity and HLA class I high‐binding candidate epitopes, pointing to novel directions for explaining metastasis.